Securing Distributed Systems in Government and Public Sector: A Technical Overview - Rishabh Gupta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the critical aspects of securing distributed systems within government and public sector organizations. It examines the implementation of comprehensive security frameworks, including Zero Trust Architecture, Artificial Intelligence-driven threat detection, and advanced identity management solutions. The article discusses the challenges faced by federal agencies in protecting sensitive data across interconnected systems while maintaining operational efficiency. It addresses key areas including identity verification, network segmentation, and resource protection, along with practical applications in digital identity platforms and emergency response systems. Through detailed analysis of security controls, compliance requirements, and emerging technologies, the article demonstrates how modern security approaches enhance the protection of government digital infrastructure while enabling secure inter-agency collaboration and public service delivery.